A prospective evaluation of chronic Babesia microti infection in seroreactive blood donors. Issue 7 (17th May 2016) - Bloch, Evan M.; Levin, Andrew E.; Williamson, Phillip C.; Cyrus, Sherri; Shaz, Beth H.; Kessler, Debra; Gorlin, Jed; Bruhn, Roberta; Lee, Tzong‐Hae; Montalvo, Leilani; Kamel, Hany; Busch, Michael P.
Abstract : BACKGROUND: Babesia microti is the foremost infectious risk to the US blood supply for which a Food and Drug Administration (FDA)‐licensed test is unavailable for donation screening. Characterization of the antibody response to B. microti and correlation with parasitemia is necessary to guide screening and donor management policies. STUDY DESIGN AND METHODS: During an FDA licensure trial, blood donors were prospectively screened (July‐November 2013) using a B. microti‐ specific antibody enzyme immunoassay (EIA, Immunetics) in highly endemic (New York [NY]; n = 13, 688), moderately endemic (Minnesota [MN]; n = 4583), and nonendemic (New Mexico [NM]; n = 8451) regions. Blood donors with repeat‐reactive (RR) results participated in a 12‐month prospective cohort study using B. microti EIA, immunofluorescent assay, polymerase chain reaction (PCR), blood smear, and clinical questionnaire. RESULTS: Thirty‐seven (61.67%; 24 NY, seven MN, six NM) of 60 eligible RR donors enrolled in the study; 20 of 37 (54%) completed the 12‐month follow‐up visit of which 15 (75%) were still seroreactive. Nine PCR‐positive donors were identified during index screening; five participated in the follow‐up study, three were PCR positive at 6 months, and two remained positive at final follow‐up (378 and 404 days). Most RR donors displayed low‐level seroreactivity that was either stable or waning during follow‐up. The level and pattern of reactivity correlated poorly with PCR positivity. CONCLUSION: The findings indicate prolonged seropositivity in blood donors. Although rare, asymptomatic, persistent PCR positivity supports the current policy of indefinite deferral for donors with a history of babesiosis or positive test results. Repeat testing by PCR and serology will be necessary if reinstatement is to be considered.